Association between salivary amylase enzyme activity and obesity in Saudi Arabia - Aldossari, Norah Mubarak (Medicine (Baltimore), 2019)
Obesity is a significant public health concern that predisposes individuals to a high risk of premature mortality. Previous studies also reported that low serum concentrations of AMY1 have been associated with obesity. The aimed of the study to assess the relationship between salivary amylase (AMY1) activity and body mass index (BMI) in Saudi male and female adults in Riyadh. This study included a total of 200 (100 individuals who were overweight and obese and 100 who had normal body weight [control individuals]) Saudi participants aged 20 to 50 years old. They were recruited from physical fitness clubs and were school employees in Riyadh City. The dietary food intake was assessed using a 24-hour dietary recall. The activity of the AMY1 was measured using a microplate fluorescence reader. A significant (P ≤ .05) increase was observed in the incidence of hypertension, dyslipidemia, diabetes mellitus (DM), and family history of overweight and obesity in overweight and obese individuals than in the control individuals, and these were in parallel to the significant increase in weight, waist circumference (WC), hip circumference (HC), systolic blood pressure (SBP), diastolic blood pressure (DBP), and BMI. A significant (P ≤ .05) increase was also observed in the carbohydrate and total fat dietary intake of overweight and obese individuals in relation to the respective dietary reference intake (DRI) values. AMY1 activity was significantly lower than the reference values in the overweight and obese group. Furthermore, AMY1 activity was significantly (P ≤ .05) reverse with weight, WC, HC, and BMI in both males and females in the overweight and obese group. In conclusion, the Saudi overweight and obese population seems to be at risk of low AMY1, which correlates with their obesity.